Noradrenergic Hypothesis Linking Neurodegeneration-Based Cognitive Decline and Astroglia - Leanza, Giampiero; Gulino, Rosario; Zorec, Robert (Frontiers in Molecular Neuroscience, 2018)
In the past, manipulation of the cholinergic system was seen as the most likely therapeutic for neurodegeneration-based cognitive decline in Alzheimer’s disease (AD) (1). However, targeting the noradrenergic system also seems a promissing strategy, since more recent studies revealed that in post-mortem tissue from patients with AD and other neurodegenerative disorders there is a robust correlation between cognitive decline and loss of neurons from the Locus coeruleus (LC), a system with diffuse noradrenaline (NA) innervation in the central nervous system (CNS). Therefore, the hypothesis has been considered that increasing NA signalling in the CNS will prevent, or at least halt the progression of neurodegeneration and cognitive decline. A hallmark of the age- and neurodegeneration-related cognitive decline is reduced neurogenesis. We here discuss noradrenergic dysfunction in AD-related cognitive decline in humans and its potential involvement in AD pathology and disease progression. We also focus on animal models to allow the validation of the noradrenergic hypothesis of AD, including those based upon the immunotoxin-mediated ablation of LC based on saporin, a protein synthesis interfering agent, which offers selective and graded demise of LC neurons, Finally, we address how astrocytes, an abundant and functionally heterogeneous cell type of neuroglia maintaining homeostasis, may participate in the regulation of neurogenesis, a new strategy for preventing LC neuron loss.